PERBANDINGAN OPENVZ DENGAN KERNEL BASED VIRTUAL MACHINE (KVM) - Mukmin, Chairul ; Cholil, Widya (Universitas Bina Darma, 2018)
Server virtualization is one system that uses energy and can work simultaneously. In this study the comparison of OpenVZ based hypervisors with kernel virtual machine (KVM) hypervisors will be compared on a virtual private server (VPS) machine. The research method uses PPDIOO developed by Cisco in network system design. The phases in the PPDIOO method are Prepare, Plan, Design, Implement, Operate and Optimize. The results of this study are OpenVZ-based virtual machines are more stable than KVM because the level of efficiency of existing resources is more efficient use of OpenVZ-based virtual machines with data using 0.8% CPU performance and 589mb of memory, the level of use of KVM-based virtual machine resources is greater with 65.4% CPU performance and 2824 mb memory, OpenVZ-based virtual machines that are able to run without large resources, while KVM-based virtual machines while working together require very large resources. Keywords: Virtualisasi Server, OpenVZ, Kernel-based Virtual Machine (KVM), Virtual Private Server (VPS)